Profile of sunless tanning product users: Results from a nationwide representative survey - Diehl, Katharina; Goerig, Tatiana; Schilling, Laura; Greinert, Ruediger; Breitbart, Eckhard W.; Schneider, Sven (Photodermatology Photoimmunology & Photomedicine, 2019)
Background: Sunless tanning products (STPs) are often seen as “healthy alternative” to sunbathing and indoor tanning. However, STP use may entail indirect risks such as overestimating an individual's natural skin type, resulting in risky (natural and artificial) tanning behavior. We aimed to explore STP use in combination with other health-related risk behaviors (eg, smoking), skin cancer risk, risk awareness of ultraviolet radiation, and preventive behavior. Methods: We used data from the NCAM, a nationwide representative cross-sectional sample (n = 3000, aged 14-45, 48.6% female) interviewed via telephone. Differences between STP users and nonusers regarding the abovementioned aspects were identified using chi²-test. Results: The 1-year prevalence of STP use was 7.5%. Tanning bed users showed a higher prevalence of STP use than past and never users (16.1% vs 9.6% vs 5.8%, P < 0.05). Although STP users had a higher skin cancer risk based on individual characteristics, they were less likely to have participated in a skin cancer screen. Conclusion: The identified parallel use of STPs and tanning beds can have severe health consequences, since the “fake tan” of STPs may lead to an overestimation of the individual's skin type, which may result in overdosed UV exposure. The lower risk awareness among STP users accompanied with their higher skin cancer risk calls for target group-specific prevention.
CRIS-Team Scopus Importer:2021-12-06
Keywords: sunbathing; sunless tanning products; tanning; tanning beds; ultraviolet radiation